Condicionantes e previsibilidade da taxa de poupança das famílias Brasileiras: Evidência microeconômica com as pesquisas de orçamentos familiares do IBGE - Marcos Antonio Coutinho da Silveira; Ajax Reynaldo Bello Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The paper investigates the demographic and socioeconomic determinants of aggregate savings rate of Brazilian families in the recent past. The main results are consistent with the predictions of the theory of the cycle of life/permanent income, properly extended to incorporate institutional and structural aspects of the Brazilian economy today, such as credit restrictions, particularly for the poorest sections of the population, comprehensive Public retirement schemes and government transfers. It is evident the importance of the cycle of life and transitory shocks on current income to account for fluctuations in the savings rate. They are also found evidence for the existence of saving for precautionary reasons. The database used in the study was produced by Household Research Budgets for 2002-2003 and 2008-2009. Although it is the only source of microeconomic observation savings of Brazilian families, this research has no annual frequency. Thus, the work applies the decomposition of Blinder-Oaxaca to assess the empirical relevance of the projection of aggregate savings of Brazilian families from econometric models estimated with data produced by research from previous years. The results show a significant instability of the estimated coefficients, as a result of changes in the response of household savings decisions to their demographic and socioeconomic characteristics, which implies savings projections do not fully reliable.
Keywords: C01; E21; 330; household savings; Blinder-Oaxaca decomposition